2017
DOI: 10.1001/jamaophthalmol.2017.4983
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Severity of Diabetic Retinopathy and Falls in an Asian Population With Diabetes

Abstract: IMPORTANCEThe presence and severity of diabetic retinopathy (DR) may contribute to the risk of falling in persons with diabetes, but evidence is currently equivocal.OBJECTIVE To investigate the associations of diabetes and DR severity with the likelihood of falls in a multiethnic Asian population. DESIGN, SETTING, AND PARTICIPANTS Cross-sectional post hoc analysis of the Singapore Epidemiology of Eye Diseases study, a population-based study of participants from 3 ethnic groups (3280 Malay, 3400 Indian, and 335… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
(97 reference statements)
0
21
1
Order By: Relevance
“…Balance is important for both locomotion and physical performance. Unsurprisingly, impaired vision in T2DM contributes to increased falls risk 74. In a cross-sectional analysis of the Singapore Epidemiology of Eye Diseases Study (n=9,481, aged 40–80 years), adults with T2DM and diabetic retinopathy had higher odds (OR:1.31 [95%CI:1.07–1.60]) of falling compared to individuals without diabetes in a fully adjusted model 74.…”
Section: Type 2 Diabetes Mellitus and Sarcopeniamentioning
confidence: 99%
“…Balance is important for both locomotion and physical performance. Unsurprisingly, impaired vision in T2DM contributes to increased falls risk 74. In a cross-sectional analysis of the Singapore Epidemiology of Eye Diseases Study (n=9,481, aged 40–80 years), adults with T2DM and diabetic retinopathy had higher odds (OR:1.31 [95%CI:1.07–1.60]) of falling compared to individuals without diabetes in a fully adjusted model 74.…”
Section: Type 2 Diabetes Mellitus and Sarcopeniamentioning
confidence: 99%
“…In a study, Gupta et al found that diabetes per se was not a risk factor for falls. However, the authors found an association between diabetic patients with DR and risk of falling [20], suggesting a relation between DR and postural balance.…”
Section: Diabetic Retinopathymentioning
confidence: 87%
“…Diabetic retinopathy (DR) is a common and potentially blinding microvascular complication of diabetes [20]. In a study, Gupta et al found that diabetes per se was not a risk factor for falls.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…The prevalence of falls and FoF is significantly higher in older adults with DM (ODM) than in older adults without DM (ONDM) [8,[11][12][13][14]. Microvascular complications associated with DM result in multiple impairments including sensory deficits and muscle weakness due to peripheral neuropathy [15][16][17][18], loss of visual acuity due to retinopathy [18][19][20], and impaired postural control and falls due to vestibulopathy [21][22][23]. These impairments predispose ODM to an increase in fall risk [17,20,24], falls [12,17,25], and FoF [25].…”
Section: Introductionmentioning
confidence: 99%
“…Since impaired sensation required for maintaining standing balance has been reported to vary largely among the ODM [17,18,20,23,24], it is plausible that ODM's performance on the mCTSIB may also vary among them and contribute to the degree of FoF they experienced. On the other hand, FoF may influence how well the ODM performs on the mCTSIB, particularly when they maintain standing balance on a compliant surface with their eyes closed.…”
Section: Introductionmentioning
confidence: 99%